Immunohistochemical and histochemical marker expression in the differential diagnosis of renal cell tumors - Visic, Milica; Karac, Minya; Filipovic, Jelena; Zivotic, Maja; Dundjerovic, Dusko; Jevtic, Jovan; Radojevic-Skodric, Sanja (Medical Research, 2025)
IntroductionThe most common renal cell tumors (RCTs) include clear cell renal cell carcinoma (ccRCC), ccRCC with eosinophilic component (ccRCCe), papillary RCC (pRCC), chromophobe RCC (chRCC), and renal oncocytoma (RO). Due to overlapping morphological features, immunohistochemical (IHC) and histochemical (HC) markers are crucial for accurate differential diagnosis.Materials and MethodsThis retrospective study included 237 patients. Tissue microarrays were manually prepared and stained with H&E, CAIX, AMACR, CD10, CD117, CK7, PRMT1, ZEB1, and Hale's colloidal iron. Semiquantitative analysis was performed using a BX53 microscope and scanned with a Leica-Aperio AT2 scanner.ResultsSignificant gender differences were observed (p = 0.0003), with a higher proportion of males in ccRCC, ccRCCe, and pRCC, while RO was more common in females. Tumor size varied significantly (p = 0.0041); ccRCCe tumors were the largest (73.1 mm), and RO the smallest (48.3 mm). Compared to ccRCC, ccRCCe showed lower PRMT1, ZEB1, and CAIX expression and higher CD10 expression. pRCC showed high AMACR expression. RO was strongly positive for PRMT1, ZEB1, and CD117, and negative for CK7, CD10, and Hale’s stain. Conversely, chRCC was negative for PRMT1 and ZEB1, but positive for CK7, CD117, and Hale’s stain.ConclusionThe following IHC panel may improve diagnostic accuracy: PRMT1+/ZEB1+/CK7−/Hale− for RO; CK7+/PRMT1−/ZEB1−/Hale+ for chRCC; CAIX+/CD10+/AMACR−/CK7− for ccRCC; and AMACR+ for pRCC. Demographic and clinicopathological differences highlight the importance of integrating clinical parameters into diagnosis and treatment planning.
Keywords: renal cell carcinoma; IHC staining; HC staining; differential diagnosis